The effect of concentrator reflector design on the energy conversion efficiency of bifacial solar cells - Wahyu Rizkika; Marza Ihsan Marzuki; Soni Prayogi (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
Bifacial solar cells can absorb light from both sides, front and back, so they can take advantage of light reflection from surrounding surfaces to improve energy efficiency. The main objective of this study is to optimize the design of a reflection concentrator that can maximize the amount of light received by the back surface of the bifacial solar cell, which is often less exposed than the front surface. The methodology used includes simulations and practical experiments. Simulations were carried out to determine the optimal angle and shape of the reflection concentrator, using photovoltaic modeling software. Practical experiments involved the construction of a reflection concentrator prototype and testing its performance under varying environmental conditions. The results showed that the use of a reflection concentrator can increase the total efficiency of bifacial solar cells by up to 20% compared to a system without a concentrator. In addition, optimal design also considers factors such as the reflective material used, the tilt angle, and the geographical conditions of the solar cell installation. These performance improvements show great potential in practical applications, especially in installations in urban areas and locations with limited space where maximum utilization of each side of the solar panel is essential.